Social educational skills in mothers of children/teens with type 1 diabetes mellitus - Kirchner, Luziane de Fátima; Benitez, Priscila; Tatmatsu, Daniely Ildegardes Brito; Ribeiro, Giovan Willian; Vargas, Vânia Maria; Del Prette, Zilda Aparecida Pereira (Revista de Psicologia, 2017)
The discovery of a chronic illness in childhood, as well as the routine of treatment, can impact on how parents interact with their children and consequently on the outcomes of the child's health. This study compared mothers Educational Social Skills of children and adolescents with or without Diabetes Mellitus Type 1. The assessment was done considering: Educational Social Skills Inventory to parents (IHSE-Pais), Classification Criterion Socioeconomic Brazil and the Glycemic Control (HbA1C) obtained by medical records. The results showed the ESS mothers of children and adolescents with or without diabetes are not significantly different, however, in the group of mothers with diabetic children, the variables age of mother and age of child, time of treatment and glycemic control (HbA1C) showed positive and negative correlation with the different factors of the IHSE-Pais. Data was discussed regarding its implications for intervention with diabetic children’s families and chronic diseases in general.